Kad Hari Raya - S. Mohamad, S. Othman; Mohamad, Rohani; S. Othman, Noorashikin; S. Othman, Ileana; S. Othman, Jumaah; S. Othman, S. Omar (Nil, 1984)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada